Growth and Break-Up of Methanogenic Granules Suggests Mechanisms for Biofilm and Community Development - Trego, Anna Christine; Galvin, Evan; Sweeney, Conor; Dunning, Sinéad; Murphy, Cillian; Mills, Simon; Nzeteu, Corine; Quince, Christopher; Connelly, Stephanie; Ijaz, Umer Zeeshan; Collins, Gavin (Frontiers in Microbiology, 2020)
Abstract. Methanogenic sludge granules are densely packed, small (diameter, approx. 0.5-2.0 mm) spherical biofilms found in anaerobic digesters used to treat industrial wastewaters, where they underpin efficient organic waste conversion and biogas production. Whilst each granule theoretically houses representative microorganisms from all of the trophic groups implicated in the successive and interdependent reactions of the anaerobic digestion process, parallel granules function side-by-side in digesters. Information on exactly how methanogenic granules develop will be important for precision management of environmental biotechnologies. Granules from a full-scale bioreactor were size-separated into small, medium and large granules. Laboratory-scale bioreactors were operated using only small (0.6–1 mm), medium (1–1.4 mm) or large (1.4–1.8 mm) granules, or unfractionated (naturally distributed) sludge. After >50 days of operation, the granule size distribution in each of the small, medium and large bioreactor types had diversified beyond – to both bigger and smaller than – the size fraction used for inoculation. ‘New’ granules were analysed by studying community structure based on high-throughput 16S rRNA gene sequencing. Methanobacterium, Aminobacterium, Propionibacteriaceae and Desulfovibrio represented the majority of the community in new granules. H2-using, and not acetoclastic, methanogens appeared more important, and were associated with abundant syntrophic bacteria. Multivariate integration analyses identified distinct discriminant taxa responsible for shaping the microbial communities in different-sized granules.